Primary Care Nurse Practitioner Burnout and ED Use and Hospitalizations Among Chronically Ill Medicare Beneficiaries - Lusine Poghosyan PhD; Jianfang Liu PhD; Amelia Schlak PhD, RN, AAAS; Suzanne Courtwright PhD; Kathleen Flandrick Dr PH; Apiradee Nantsupawat PhD; Grant R. Martsolf PhD (SAGE Publishing, 2023)
Nurse practitioners (NPs) represent the fastest-growing workforce of primary care clinicians in the United States. Their numbers are projected to grow in the near future. The NP workforce can help the country meet the rising demand for care services due to the aging population and increasing chronic disease burden. Yet, increased burnout among these clinicians may affect their ability to deliver high-quality, safe care. We investigated how NP burnout in primary care practices affects patient outcomes, including emergency department (ED) use and hospitalizations, among older adults with chronic conditions. In 2018-2019, we collected survey data from 1244 primary care NPs from 6 geographically diverse states on their burnout and merged the survey data with data from Medicare claims on ED use and hospitalizations among 467 466 older adults with chronic conditions. 26.3% of NPs reported burnout. Using logistic regression models, we found that with a 1-unit increase in the standardized burnout score, the odds of an ED visit increased by 2.8% (OR = 1.028; P -value = .035); Ambulatory Care Sensitive Conditions (ACSC) ED visit by 3.2% (OR = 1.032; P -value = .019); hospitalization by 3.9% (OR = 1.039; P -value = .001); and ACSC hospitalization by 6.2% (OR = 1.062; P -value = .001). Our findings indicate that if chronically ill older adults receive care in primary care practices with higher NP burnout rates they are more likely to use EDs and hospitals. Policy and practice efforts, such as improving NP working conditions, should be undertaken to reduce NP burnout in primary care practices to potentially prevent acute care use.